# Plot of three coupled oscillator.

2 visualizzazioni (ultimi 30 giorni)
Haya Ali il 19 Dic 2022
Commentato: Haya Ali il 20 Dic 2022
I am trying to built three coupled oscillator just as two coupled oscillator but i don't know what mistake I am doing. Please help me. The code for both the cases are given below
%%Two coupled
clear all; close all; clc;
%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%
% Simulation %
%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%
%value of constants
a1=0.1;a2=0.2;
omega1=5;omega2=4;
G=0.01;C12=0.001;C21=0.002;
dt=0.01; %step size
%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%
x1(1)=0.5;
y1(1)=0.5;
x2(1)=0.5;
y2(1)=0.5;
for i=2:1000
x1(i)=x1(i-1)+((a1-x1(i-1)^2-y1(i-1)^2)*x1(i-1)-omega1*y1(i-1)+G*C12*(x2(i-1)-x1(i-1)))*dt;
y1(i)=y1(i-1)+((a1-x1(i-1)^2-y1(i-1)^2)*y1(i-1)+omega1*x1(i-1)+G*C12*(y2(i-1)-y1(i-1)))*dt;
x2(i)=x2(i-1)+((a2-x2(i-1)^2-y2(i-1)^2)*x2(i-1)-omega2*y2(i-1)+G*C21*(x1(i-1)-x2(i-1)))*dt;
y2(i)=y2(i-1)+((a2-x2(i-1)^2-y2(i-1)^2)*y2(i-1)+omega2*x2(i-1)+G*C21*(y1(i-1)-y2(i-1)))*dt;
end
figure
hold on
plot(x1,'r')
plot(x2,'g')
%% Three Coupled
close all; clear all; clc;
%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%
% Simulation %
%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%
%value of constants
a1=0.1;a2=0.2;a3=0.5;
omega1=5;omega2=4;omega3=3;
G=0.01;C12=0.001;C13=0.006;
C21=0.003;C23=0.005;
C31=0.002;C32=0.004;
dt=0.01; %step size
%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%
x1(1)=0.5;
y1(1)=0.5;
x2(1)=1;
y2(1)=1;
x3(1)=1.5;
y3(1)=1.5;
for i=2:2000
x1(i)=x1(i-1)+((a1-x1(i-1)^2-y1(i-1)^2)*x1(i-1)-omega1*y1(i-1)+G*C12*(x2(i-1)-x1(i-1)))+G*C13*(x3(i-1)-x1(i-1))*dt;
y1(i)=y1(i-1)+((a1-x1(i-1)^2-y1(i-1)^2)*y1(i-1)+omega1*x1(i-1)+G*C12*(y2(i-1)-y1(i-1)))+G*C13*(y3(i-1)-y1(i-1))*dt;
x2(i)=x2(i-1)+((a2-x2(i-1)^2-y2(i-1)^2)*x2(i-1)-omega2*y2(i-1)+G*C21*(x1(i-1)-x2(i-1)))+G*C23*(x3(i-1)-x2(i-1))*dt;
y2(i)=y2(i-1)+((a2-x2(i-1)^2-y2(i-1)^2)*y2(i-1)+omega2*x2(i-1)+G*C21*(y1(i-1)-y2(i-1)))+G*C23*(y3(i-1)-y2(i-1))*dt;
x3(i)=x3(i-1)+((a3-x3(i-1)^2-y3(i-1)^2)*x3(i-1)-omega3*y3(i-1)+G*C31*(x1(i-1)-x3(i-1)))+G*C32*(x2(i-1)-x3(i-1))*dt;
y3(i)=y3(i-1)+((a3-x3(i-1)^2-y3(i-1)^2)*y3(i-1)+omega3*x3(i-1)+G*C31*(y1(i-1)-y3(i-1)))+G*C32*(y2(i-1)-y3(i-1))*dt;
end
figure
hold on
plot(x1,'r')
plot(x2,'g')
plot(x3,'m')
##### 0 CommentiMostra -2 commenti meno recentiNascondi -2 commenti meno recenti

Accedi per commentare.

### Risposta accettata

Sam Chak il 19 Dic 2022
I don't know what oscillators are since you didn't provide the math equations to compare with. However, on the programming side, it appears that the location of parenthesis caused the problem. It is possible to randomly shuffle the locations of the brackets by some algorithms until the system responses are stable.
Check if these are the expected responses.
% value of constants
a1 = 0.1;
a2 = 0.2;
a3 = 0.5;
omega1 = 5;
omega2 = 4;
omega3 = 3;
G = 0.01;
C12 = 0.001;
C13 = 0.006;
C21 = 0.003;
C23 = 0.005;
C31 = 0.002;
C32 = 0.004;
dt = 0.01; % step size
%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%
x1(1) = 0.5;
y1(1) = 0.5;
x2(1) = 1;
y2(1) = 1;
x3(1) = 1.5;
y3(1) = 1.5;
for i = 2:1000
% x1(i) = x1(i-1) + ((a1 - x1(i-1)^2 - y1(i-1)^2)*x1(i-1) - omega1*y1(i-1) + G*C12*(x2(i-1) - x1(i-1))) + G*C13*(x3(i-1) - x1(i-1))*dt;
% y1(i) = y1(i-1) + ((a1 - x1(i-1)^2 - y1(i-1)^2)*y1(i-1) + omega1*x1(i-1) + G*C12*(y2(i-1) - y1(i-1))) + G*C13*(y3(i-1) - y1(i-1))*dt;
% x2(i) = x2(i-1) + ((a2 - x2(i-1)^2 - y2(i-1)^2)*x2(i-1) - omega2*y2(i-1) + G*C21*(x1(i-1) - x2(i-1))) + G*C23*(x3(i-1) - x2(i-1))*dt;
% y2(i) = y2(i-1) + ((a2 - x2(i-1)^2 - y2(i-1)^2)*y2(i-1) + omega2*x2(i-1) + G*C21*(y1(i-1) - y2(i-1))) + G*C23*(y3(i-1) - y2(i-1))*dt;
% x3(i) = x3(i-1) + ((a3 - x3(i-1)^2 - y3(i-1)^2)*x3(i-1) - omega3*y3(i-1) + G*C31*(x1(i-1) - x3(i-1))) + G*C32*(x2(i-1) - x3(i-1))*dt;
% y3(i) = y3(i-1) + ((a3 - x3(i-1)^2 - y3(i-1)^2)*y3(i-1) + omega3*x3(i-1) + G*C31*(y1(i-1) - y3(i-1))) + G*C32*(y2(i-1) - y3(i-1))*dt;
x1(i) = x1(i-1) + ( ( a1 - x1(i-1)^2 - y1(i-1)^2 )*x1(i-1) - omega1*y1(i-1) + G*C12*( x2(i-1) - x1(i-1) ) + G*C13*( x3(i-1) - x1(i-1) ) )*dt;
y1(i) = y1(i-1) + ( ( a1 - x1(i-1)^2 - y1(i-1)^2 )*y1(i-1) + omega1*x1(i-1) + G*C12*( y2(i-1) - y1(i-1) ) + G*C13*( y3(i-1) - y1(i-1) ) )*dt;
x2(i) = x2(i-1) + ( ( a2 - x2(i-1)^2 - y2(i-1)^2 )*x2(i-1) - omega2*y2(i-1) + G*C21*( x1(i-1) - x2(i-1) ) + G*C23*( x3(i-1) - x2(i-1) ) )*dt;
y2(i) = y2(i-1) + ( ( a2 - x2(i-1)^2 - y2(i-1)^2 )*y2(i-1) + omega2*x2(i-1) + G*C21*( y1(i-1) - y2(i-1) ) + G*C23*( y3(i-1) - y2(i-1) ) )*dt;
x3(i) = x3(i-1) + ( ( a3 - x3(i-1)^2 - y3(i-1)^2 )*x3(i-1) - omega3*y3(i-1) + G*C31*( x1(i-1) - x3(i-1) ) + G*C32*( x2(i-1) - x3(i-1) ) )*dt;
y3(i) = y3(i-1) + ( ( a3 - x3(i-1)^2 - y3(i-1)^2 )*y3(i-1) + omega3*x3(i-1) + G*C31*( y1(i-1) - y3(i-1) ) + G*C32*( y2(i-1) - y3(i-1) ) )*dt;
end
figure
hold on
plot(x1)
plot(x2)
plot(x3)
grid on, legend('x', 'y', 'z')
##### 4 CommentiMostra 2 commenti meno recentiNascondi 2 commenti meno recenti
Sam Chak il 19 Dic 2022
This is another version in 3-D.
% value of constants
a1 = 0.1;
a2 = 0.2;
a3 = 0.5;
omega1 = 5;
omega2 = 4;
omega3 = 3;
G = 0.01;
C12 = 0.001;
C13 = 0.006;
C21 = 0.003;
C23 = 0.005;
C31 = 0.002;
C32 = 0.004;
dt = 0.01; % step size
%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%
x1(1) = 0.5;
y1(1) = 0.5;
x2(1) = 1;
y2(1) = 1;
x3(1) = 1.5;
y3(1) = 1.5;
for i = 2:6000
x1(i) = x1(i-1) + ( ( a1 - x1(i-1)^2 - y1(i-1)^2 )*x1(i-1) - omega1*y1(i-1) + G*C12*( x2(i-1) - x1(i-1) ) + G*C13*( x3(i-1) - x1(i-1) ) )*dt;
y1(i) = y1(i-1) + ( ( a1 - x1(i-1)^2 - y1(i-1)^2 )*y1(i-1) + omega1*x1(i-1) + G*C12*( y2(i-1) - y1(i-1) ) + G*C13*( y3(i-1) - y1(i-1) ) )*dt;
x2(i) = x2(i-1) + ( ( a2 - x2(i-1)^2 - y2(i-1)^2 )*x2(i-1) - omega2*y2(i-1) + G*C21*( x1(i-1) - x2(i-1) ) + G*C23*( x3(i-1) - x2(i-1) ) )*dt;
y2(i) = y2(i-1) + ( ( a2 - x2(i-1)^2 - y2(i-1)^2 )*y2(i-1) + omega2*x2(i-1) + G*C21*( y1(i-1) - y2(i-1) ) + G*C23*( y3(i-1) - y2(i-1) ) )*dt;
x3(i) = x3(i-1) + ( ( a3 - x3(i-1)^2 - y3(i-1)^2 )*x3(i-1) - omega3*y3(i-1) + G*C31*( x1(i-1) - x3(i-1) ) + G*C32*( x2(i-1) - x3(i-1) ) )*dt;
y3(i) = y3(i-1) + ( ( a3 - x3(i-1)^2 - y3(i-1)^2 )*y3(i-1) + omega3*x3(i-1) + G*C31*( y1(i-1) - y3(i-1) ) + G*C32*( y2(i-1) - y3(i-1) ) )*dt;
end
figure
hold on
plot3(x1, x2, x3)
view(45, 30)
Haya Ali il 20 Dic 2022
Thank you for the efforts Sam :)

Accedi per commentare.

### Categorie

Scopri di più su Performance and Memory in Help Center e File Exchange

### Community Treasure Hunt

Find the treasures in MATLAB Central and discover how the community can help you!

Start Hunting!

Translated by